An Iterative Method for the Uniformity Improvement of Edge-Lit Backlight. (28th September 2016) - Yan, Jin-Ren; Li, De-Cong; Wang, Zhi-Kun; Rao, Wen-Ping
Abstract : A simple iterative optimization method is developed to improve the exiting light uniformity of the edge-lit backlight module. The method uses the relative deviation of the average luminous flux of the entire light guide plate (LGP) and the luminous flux of each region as constraint criterion and the ratio of the luminous flux of each region to the average luminous flux of the LGP as adjustment coefficient to adjust the density of the microstructures in each region. This process loops until the relative deviations of all regions meet a prespecified threshold value. A LGP based on microprism structure is presented to validate the method. The initial values, which represent the size of the microstructures manufactured on the bottom surfaces of the LGP, d 0 -dependent luminous fluxes, microstructure size distributions, iterations of the LGP, and the relative deviation of each region are discussed. The simulation results show that it is a very practical method for the uniformity improvement of the backlight when an appropriate initial value is selected and the final uniformity is better than 90% after optimization.